Contrast Induced Nephropathy in Diabetic and Non-diabetic Patients during Coronary Angiogram and Angioplasty - Rahman, MM; Haque, HS; Banerjee, SK; Ahsan, SA; Rahman, MF; Mahmood, M; Salman, M; Azam, MG (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):372-6 The abstract of this article is available on the PubMed website